Green Theology in the Qur’an: A Linguistic and Scientific Study on Earth’s Water Reservoirs - Sujiat Zubaidi; Aqdi Rofiq Asnawi; Muhammad Dini Syauqi Al-Madani; Ide Mafaza Sansayto (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
Water is a vital element that sustains life and maintains the balance of the global ecosystem. This article examines the correlation between the Earth’s water reservoirs and environmental preservation as indicated in the Qur’an. The study employs a semantic analysis method within the framework of iʿjāz lughawī (linguistic inimitability) and iʿjāz ʿilmī (scientific inimitability), focusing on key verses from Surah al-Ḥijr (15:22) and al-Mu’minūn (23:18–19), and is supported by an interdisciplinary literature review. The findings reveal that the term asqaynā refers to the process of water infiltration into the soil, while askannā denotes the mechanism of subterranean water storage. These terms represent a complex hydrological cycle, encompassing rainfall, infiltration, percolation, and plant absorption. This process supports photosynthesis, maintains soil moisture, and enhances ecological stability sustainably. The study concludes that the Qur’an not only conveys spiritual and moral teachings, but also contains scientific insights aligned with the principles of environmental sustainability. It contributes to the development of ecological Qur’anic exegesis rooted in integrating scientific knowledge and divine revelation.